THE EFFECT AT MUSCLE POWER ARM, HAND-EYE COORDINATION, FLEXIBILITY AND SELF CONFIDENCE UPON BADMINTON SMASH SKILL - Myrza Akbari; Firmansyah Dlis; Widiastuti Widiastuti (Program Pascasarjana Universitas Negeri Jakarta, 2017)
This study aims to reveal whether there is effect muscle power arm, hand eye coordination, flexibility and confidence to smash badminton skills, either directly or indirectly. The research was conducted at the Serambi Mekkah University, with a sample consisting of 73 samples were selected from 677 students from the Serambi Mekkah University penjaskesrek program.. The analysis technique used in this research is using path analysis (path analysis), with the aim to identify the direct and indirect effect between variables. The results showed that: (1) Arm muscle power directly effect the confidence of 4.62%, (2) Hand-eye coordination has a direct effect on confidence of 59.29%. (3) Flexibility of the torso indirectly effect the confidence of 92.69%, (4) Arm muscle power indirectly effect badminton smash skills of 66.55%. (5) Eye-hand coordination directly effects badminton smash skills by 8.64%, (6) Flexibility of the torso directly effects badminton smash skills by 10.43%, (7) Confidence directly effects badminton smash skills of 14.90%. Keywords:Badminton smash skills, muscle power arm, hand- eye coordination, flexibility, confident